PATHOS, VECTORS, MIST. - BAJOHR, HANNES (Michigan Quarterly Review)
The article focuses on the intersection of programming, language, and emotion, questioning whether pathos—or human feeling—can be expressed through code. Topics include the linguistic limitations of programming languages, the aesthetic and rhetorical potential of code as a literary form, and the role of code poetry in bridging human expression with machine logic.